Study on the development and application of a felling rate prediction model in forest construction design - Nam, Pak Jong; Hyok, An; Myong, Mun Gwang (International Journal of Architecture and Urbanism, 2026)
The work of mapping the long-term plan into a scientific calculation of the management objectives of forests, survey, maturity, felling age, felling rate, scale and cycle of production is an important requirement for protecting the ecological environment of forests and increasing their economic effectiveness. This paper presents a problem of predicting the tree-felling rate, or a technical reference calculation for forest construction planning by means of a grey mathematical method. Quantitative predictions of felling rate can be analyzed by various models, such as time series model, regression model, grey model, neural network model, Markov model, etc. We do not need to have a large amount of reliable data on the basis of the data, and consider how the calculation method can be predicted by applying a simple, high-accuracy grey model.